2023
DOI: 10.1186/s12943-023-01749-3
|View full text |Cite
|
Sign up to set email alerts
|

The epigenetic regulatory mechanism of PIWI/piRNAs in human cancers

Abstract: PIWI proteins have a strong correlation with PIWI-interacting RNAs (piRNAs), which are significant in development and reproduction of organisms. Recently, emerging evidences have indicated that apart from the reproductive function, PIWI/piRNAs with abnormal expression, also involve greatly in varieties of human cancers. Moreover, human PIWI proteins are usually expressed only in germ cells and hardly in somatic cells, so the abnormal expression of PIWI proteins in different types of cancer offer a promising op… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(14 citation statements)
references
References 134 publications
0
14
0
Order By: Relevance
“…It has been widely reported that liposome is an ideal platform for fat‐soluble drug loading and slow release. [ 27 ] Hyaluronic acid and gelatin, as the major component of ECM, have proven effective in regulating key cellular processes and behaviors, including proliferation, differentiation, and the inflammatory response, [ 28 ] which may contribute to cellular reprogramming. [ 29 ] Adhesive seed microsphere AFHS with TiT cocktail nucleus and positively charged surface modification were developed through liposome nanodrug carrier system, microfluidic technology, photoresponsive crosslinking technology, and poly allylamine hydrochloride (PAH) activation (Figure 2f).…”
Section: Resultsmentioning
confidence: 99%
“…It has been widely reported that liposome is an ideal platform for fat‐soluble drug loading and slow release. [ 27 ] Hyaluronic acid and gelatin, as the major component of ECM, have proven effective in regulating key cellular processes and behaviors, including proliferation, differentiation, and the inflammatory response, [ 28 ] which may contribute to cellular reprogramming. [ 29 ] Adhesive seed microsphere AFHS with TiT cocktail nucleus and positively charged surface modification were developed through liposome nanodrug carrier system, microfluidic technology, photoresponsive crosslinking technology, and poly allylamine hydrochloride (PAH) activation (Figure 2f).…”
Section: Resultsmentioning
confidence: 99%
“…Recent research into piRNA dysregulation across various cancers has highlighted its in uential role in facilitating tumor cell growth, proliferation, metastasis, and progression [21][22][23] . Compared to other noncoding RNAs, piRNAs exhibit superior speci city, deliverability, and tolerability within tumors, which makes them the optimal targets for cancer therapy [51,52] . PiRNAs, with their profound impact on epigenetic regulation, are emerging as pivotal diagnostic markers and therapeutic avenues across a spectrum of malignancies.…”
Section: Discussionmentioning
confidence: 99%
“…The genome sequences coding for certain piRNA classes are often found within proteincoding genes, and functional piRNAs are predominantly produced from the 3 -untranslated regions (3 -UTRs) of mRNA during translation [77]. Furthermore, these mRNA 3 -UTRs, which produce piRNAs, often contain transposon sequences whose activity is regulated by these piRNAs at the post-transcriptional level [78].…”
Section: Discussionmentioning
confidence: 99%